Analisis Pelanggaran Etika Periklanan Studi Kasus Iklan Billboard Le Minerale di Kota Bandung - Hasnah Khonsa; Amanda Noviyanti; Alma Aninditha Zalianty; Daniel Handoko (STIKes Ibnu Sina Ajibarang, 2024)
This research examines violations of advertising ethics in Le Minerale billboard advertisements in the city of Bandung which exploit children. The advertisement may use images or situations of children in a manner that is inappropriate or inconsistent with applicable social or cultural norms. This research aims to investigate, describe in depth the violations of advertising ethics that occurred in Le Minerale billboard advertisements in the city of Bandung and also analyze the implications of these violations for more moral advertising practices in the future. It is hoped that the results of this research will provide deeper insight into ethical advertising practices.